Defining control reference ranges in biologic samples in analytical laboratories - Vrugt, Bart; Kuhn, Barbara K.; Attanoos, Richard (Frontiers in Public Health, 2025)
Mineral analytic laboratories define control reference ranges to interpret the significance of an individual’s prior exposures. Control reference ranges are internally compiled and defined for two scenarios: background controls—only subjects with ambient asbestos exposure and no increased risk of asbestos related disease, and asbestosis range controls, utilized for the diagnosis of asbestos-related lung fibrosis/asbestosis and for asbestos-related lung cancer causation. The objective of this study was to evaluate how different analytic laboratories have established their internal control reference ranges and to comment on their significance. The study comprised a review of the scientific literature generated from a Pubmed search of mineral analytic data from lung tissue in laboratories determining background exposures to asbestos and other elongate minerals. Twenty-six publications were found from 17 laboratories across Europe, North America, and Asia which had internally defined background control populations. The studies showed marked heterogeneity having been conducted over decades, using different criteria, different microscopic methodologies, and assessment of different fiber dimension. The most common criterion to define background control subjects was to establish individuals with no known occupational history of asbestos exposure and/or no evidence of asbestos-related diseases. In background controls with no disease, chrysotile was reported most frequently. Chrysotile and amphiboles were variably detected in lung tissue from control subjects in virtually all studies. Interlaboratory variations exist so individual results obtained in one laboratory do not transfer significance to another laboratory. The use of negative control groups in case–control studies is discussed alongside their relevance in ensuring the validity of results related to asbestos exposure and its diseases.